Migration effects on the intestinal microbiota of Tibetans - Tian Liang; Fang Liu; Lifeng Ma; Zhiying Zhang; Lijun Liu; Tingting Huang; Jing Li; Wenxue Dong; Han Zhang; Yansong Li; Yaqiong Jiang; Weimin Ye; et al. (PeerJ, 2021)
Background Diet, environment, and genomic context have a significant impact on humans’ intestinal microbiota. Moreover, migration may be accompanied by changes in human eating habits and living environment, which could, in turn, affect the intestinal microbiota. Located in southwestern China, Tibet has an average altitude of 4,000 meters and is known as the world’s roof. Xianyang is situated in the plains of central China, with an average altitude of about 400 meters. Methods To understand the association between intestinal microbiota and population migration, we collected the fecal samples from 30 Tibetan women on the first day (as TI1st), six months (as TI2nd), and ten months (as TI3rd) following migration from Tibet to Xianyang. Fecal samples were collected from 29 individuals (belonging to the Han women) as a control. The dietary information of the Tibetan women and the Han women was gathered. We performed a 16S rRNA gene survey of the collected fecal samples using Illumina MiSeq sequencing. Results Following the migration, the alpha and beta diversity of Tibetan women’s intestinal microbiota appeared unaffected. Linear discriminant analysis effect size (LEfSe) analysis showed that Klebsiella, Blautia, and Veillonella are potential biomarkers at TI1st, while Proteobacteria and Enterobacteriaceae were common in TI3rd. Finally, functional prediction by phylogenetic investigation of communities by reconstruction of unobserved states (PICRUSt) found no significant up-regulation or down-regulation gene pathway in the intestinal microbiota of Tibetan women after migration. The present study reveals that the higher stability in Tibetan women’s intestinal microbiota was less affected by the environment and diet, indicating that Tibetan women’s intestinal microbiota is relatively stable. The main limitations of the study were the small sample size and all volunteers were women.